Hubungan Posisi Menyusui dan Perawatan Payudara dengan Kejadian Bendungan ASI di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Puja Rahma Tifanni; Desi Pramita Sari; Renny Adelia Tarigan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Breast milk dam is a swelling of the breast due to an increase in venous and lymph flow, causing breast milk dam. Data (SDKI) showed that 42% of mothers experienced breast milk dams. Breast milk dams are caused by discontinuous breastfeeding, the baby has not breastfed properly, improper breastfeeding position, wearing BH that is too tight, nipple abnormalities, absence of breast care before and after childbirth and lack of maternal knowledge about breast care. The aim is to determine the relationship between breastfeeding position and breast care with the incidence of breast milk dam in the working area of Sei.Langkai Health Center, Batam City 2023. The method in this study used quantitative research with analytical descriptive research and used a Cross Sectional research design, the sample in this study was 65 postpartum women, statistical tests using Chi-Square, purposive sampling technique. The distribution of breastfeeding positions was not correct as many as 36 postpartum women (55.4%), postpartum women did not perform breast care as many as 55 postpartum women (84.6%), the majority of postpartum women who experienced breast milk dams were 36 postpartum women (55.4%). The results of statistical analysis with Chi-Square found that there was no relationship between breastfeeding position and the incidence of breast milk dam with a value (P-Value) = 0.099 where (P < ?) = 0.05, and there was a relationship between breast care and the incidence of breast milk dam with a value (P-Value) = 0.030 where (P < ?) = 0.05. The conclusion is that there is no relationship between breastfeeding position and the incidence of breast milk dam and there is a relationship between breastfeeding position and breast milk dam. it is hoped that midwives and other health workers can teach mothers directly during breastfeeding how to do the correct breastfeeding position and breast care technique.